Istilah-Istilah Pakaian Dan Perhiasan Pengantin Pria Adat Lampung Pepadun - Dimas Bagus Editya (Institut Penelitian dan Pengembangan Mandalika (IP2MI), 2025)
This research will analyze the terms of clothing and jewelry for the Lampung Pepadun traditional groom using a semantic study approach. This research describes and examines the lexical semantic meaning relationships contained in the terms of Lampung Pepadun traditional groom's clothing and looks at the meaning of the concepts contained therein. What is used in this research is a qualitative method. The data collection technique uses note-taking and recording techniques. The research data source is in the form of terms for Lampung traditional groom's clothing obtained from sources, namely Lampung cultural figures who understand the ins and outs of Lampung culture. The theory used in this research refers to the theory of Djadjasudarma, Tajudin Nur, and